Histopathological alterations induced in the liver of an estuarine mullet, Liza parsia by mercuric Chloride and DDT - Pandey, A K; George, K C; Mohamed, M Peer (Indian Journal of Fisheries, 2011)
Liza parsia were exposed to HgCl2 (acute, 1.0 ppm; sublethal, 0.5 ppm) andDDT (acute, 0.1 ppm) for 15 days. In control mullets, the liver was comprisedof polygonal hepatocytes with centrally placed nucleus. Exposures to HgCl2and DDT induced dilation of blood sinusoids, vacuolization and granulardegeneration of hepatocytes. The complete necrosis of hepatocytes at places(focal necrosis) and fibrosis were noticed on day 15 in the experimental fishes.Blood sinusoids also depicted complete disorganization by close of theexperiment.